2016
DOI: 10.1002/anie.201511711
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Fast Protein Dynamics from NMR Chemical Exchange Saturation Transfer Data

Abstract: Functional motions of 15N-labeled proteins can be monitored by solution NMR spin relaxation experiments over a broad range of timescales. These experiments however typically take of the order of several days to a week per protein. Recently, NMR chemical exchange saturation transfer (CEST) experiments have emerged to probe slow millisecond motions complementing R1ρ and CPMG-type experiments. CEST also simultaneously reports on site-specific R1 and R2 parameters. It is shown here how CEST-derived R1, R2 relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…k ex = 50–150 s −1 ). The CEST experiment can also simultaneously take advantage of the CEST-derived R 1 and R 2 data to extract S 2 order parameters reporting on the ps-ns time scale 30 . In spin-relaxation NMR, the order parameter S 2 is typically extracted from the model-free approach using experimental R 1 , R 2 , and hNOE NMR data 3133 .…”
Section: Investigating the Microsecond To Millisecond Time Frame Tmentioning
confidence: 99%
“…k ex = 50–150 s −1 ). The CEST experiment can also simultaneously take advantage of the CEST-derived R 1 and R 2 data to extract S 2 order parameters reporting on the ps-ns time scale 30 . In spin-relaxation NMR, the order parameter S 2 is typically extracted from the model-free approach using experimental R 1 , R 2 , and hNOE NMR data 3133 .…”
Section: Investigating the Microsecond To Millisecond Time Frame Tmentioning
confidence: 99%
“…Recent advances employing saturation transfer, such as chemical exchange saturation transfer (CEST) and dark-state exchange saturation transfer (DEST), have enabled the detection of these previously invisible protein states [7, 8]. Several studies have already reported the use of CEST to study the invisible conformers of slowly exchanging proteins on the millisecond to second timescale [1, 912]. Additionally, the fitting of CEST profiles have been shown to reliably extract R 1 and R 2 parameters that can be used for modelfree analysis of fast timescale dynamics (ps to ns).…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, no study has combined CEST-derived R 1 and R 2 parameters with 1 H- 15 N NOE data to establish the picosecond to nanosecond dynamics of a protein. Instead, leaner versions of modelfree have been applied without the NOE data [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, an additional local R ex parameter is also fit to obtain information about slower timescale dynamics arising from conformational exchange which increases the minimum number of necessary experimental observables to 3 n +1 for the case of isotropic tumbling. So-called “lean” approaches (Gu, Hansen, Peng, & Bruschweiler, 2016) can be used to reduce data collection and a recent publication has provided a systematic and quantitative evaluation of using a reduced number of 15 N relaxation observables in the quantification of internal motion (Jaremko, Jaremko, Ejchart, & Nowakowski, 2018). Alternative methods utilizing cross correlated relaxation have also been introduced but will not be discussed further here (Pelupessy, Espallargas, & Bodenhausen, 2003; Reif, Diener, Hennig, Maurer, & Griesinger, 2000; Weaver, & Zuiderweg, 2008; Weaver, & Zuiderweg, 2009).…”
Section: Nmr Spin Relaxation Methodsmentioning
confidence: 99%